Planning, preparing and structuring a small group teaching session - van Diggele, Christie (BMC Med Educ, 2020)
A structured approach is critical to the success of any small group teaching session; preparation and planning are key elements in ensuring the session is systematic and effective. Learning activities guide and engage students towards the achievement of agreed learning outcomes. This paper introduces the central concepts of planning and preparing a small group teaching session. It provides an overview of key theoretical principles in lesson planning, delivery, and how to provide effective feedback in this setting.